POWDER-GAS DISCHARGE, FORMED AT MELTING OF ALUMINIUM CASTING ALLOYS IN INDUCTION CRUCIBLE FURNACE IAT- 6 - G. A. Rumjantseva; B. M. Nemenenok; S. P. Zadrutskiy (Литьë и металлургия)
The carried out analysis of powder-gas discharge shows that volumes and composition of the forming dust are determined by composition of recycled material, type of lubrication for machines under high pressure, quality of recycled material preparation and technology of refining processing.